Ion beam therapy: fundamentals, technology, clinical applications - Linz, Ute (Biological and Medical Physics, Biomedical Engineering,, 2012)
The book provides a detailed, up-to-date account of the basics, the technology, and the clinical use of ion beams for radiation therapy. Theoretical background, technical components, and patient treatment schemes are delineated by the leading experts that helped to develop this field from a research niche to its current highly sophisticated and powerful clinical treatment level used to the benefit of cancer patients worldwide. Rather than being a side-by-side collection of articles, this book consists of related chapters. It is a common achievement by 76 experts from around the world. Their expertise reflects the diversity of the field with radiation therapy, medical and accelerator physics, radiobiology, computer science, engineering, and health economics. The book addresses a similarly broad audience ranging from professionals that need to know more about this novel treatment modality or consider to enter the field of ion beam therapy as a researcher. However, it is also written for the interested public and for patients who might want to learn about this treatment option.